Testing factorial invariance of the questionnaire of evaluation of the quality perceived in sports services in Spanish, Ecuadorian and Colombian users - Gálvez Ruiz, Pablo; Conde-Pascual, Elena; Estrella-Andrade, Alexandra; García Fernández, Jerónimo; Romero-Galisteo, Rita Pilar; Vélez-Colón, Luisa; Pitts, Brenda (Springer Nature, 2021)
The Questionnaire of Evaluation of the Quality Perceived in Sports Services is a quantitative tool that has mainly been developed in users of public sports services. The aim of this study was to adapt the tool and determine the psychometric properties and the degree of factorial equivalence in three different countries (Spain, Ecuador and Colombia). Using a convenience sampling strategy, three samples with a total of 927 participants were analyzed, of which 330 were spanish, 363 ecuadorians and 234 colombians. The CFA ratified the original structure of 25 items and showed a good fit to the data in the Spanish, Colombian and Ecuadorian sample. All constructs presented good internal consistency, convergent and discriminant validity. Lastly, a multi-group analysis showed the invariance factorial through the difference in the RMSEA, CFI and NNFI indices. The findings of the present study demonstrated evidence for the instrument validity and reliability. In conclusion, the adapted version of the tool provide insightful implications for sport management professionals for the evaluation of the quality of sport services in different countries who have the Spanish language as their mother tongue.
https://openpolicyfinder.jisc.ac.uk/id/publication/15760
Keywords: Instalaciones deportivas - Gestión de la calidad; Sports services; Perceived quality; Factorial structure; Factorial invariance; Sport management